AYURVEDA FOR PROMOTION OF HEALTH - Vijay Kumar; Mishra, Mriganka; Rymbai, D. Walebai R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health is self produced by equilibrium and balance in the behavior of individuals at every level. This is the real meaning of wellbeing advancement on public health according to Ayurveda. Ayurveda is based on universal principles -- not constrained to a specific ethnic gathering or culture-being both individual focused and intercultural and it very well may be utilized as a joining of the existent human services frameworks just as a layout to safeguard nearby conventional qualities so as to address the issues of various populaces. Ayurveda concerns mostly with longevity, whose notion is not only limited merely to long-lasting life, but it encompasses all the conditions to live in health and vitality in order to achieve an healthy death, meaning the natural final experience of the cycle of life. Thus, in Ayurveda the concept of public health, even encompassing all ages, focuses primarily on the individual capability of healthy aging intended as complete fulfilling one’s life.